Allergen extract vs. component sensitization and airway inflammation, responsiveness and new‐onset respiratory disease. Issue 5 (May 2016) - Patelis, A.; Gunnbjornsdottir, M.; Alving, K.; Borres, M. P.; Högman, M.; Janson, C.; Malinovschi, A.
Summary: Background: The absence of IgE sensitization to allergen components in the presence of sensitization to the corresponding extract has been reported, but its clinical importance has not been studied. Objective: To evaluate the clinical significance of IgE sensitization to three aeroallergen extracts and the corresponding components in relation to the development of respiratory disease. Methods: A total of 467 adults participated in the European Community Respiratory Health Survey (ECRHS) II and 302 in ECRHS III, 12 years later. IgE sensitization to allergen extract and components, exhaled nitric oxide (FeNO) and bronchial responsiveness to methacholine were measured in ECRHS II. Rhinitis and asthma symptoms were questionnaire‐assessed in both ECRHS II and III. Results: A good overall correlation was found between IgE sensitization to extract and components for cat ( r = 0.83), timothy ( r = 0.96) and birch ( r = 0.95). However, a substantial proportion of subjects tested IgE positive for cat and timothy allergen extracts but negative for the corresponding components (48% and 21%, respectively). Subjects sensitized to both cat extract and components had higher FeNO ( P = 0.008) and more bronchial responsiveness ( P = 0.002) than subjects sensitized only to the extract. Further, subjects sensitized to cat components were more likely to develop asthma ( P = 0.005) and rhinitis ( P = 0.007) than subjects sensitized only to cat extract. Conclusion: Measurement of IgE sensitization to cat allergen components would seem to have a higher clinical value than extract‐based measurement, as it related better to airway inflammation and responsiveness and had a higher prognostic value for the development of asthma and rhinitis over a 12‐year period.